The Differences Between Management And Leadership - Wajdi, Barid Nizarudin (Economic and Bussiness Faculty, Dr Soetomo University, 2017)
There are a differences between management and leadership. The aim of this review is to determine the differences between management and leadership. The result of this review showed that management and leadership are two very distinct functions. Although, management and leadership do share many similar duties which consist of working with people and influencing others to achieve goals. Management skills are used to plan, build, and direct organizational systems to accomplish missions and goals, while leadership skills are used to focus on a potential change by establishing direction, aligning people, and motivating and inspiring. Leadership and management must go hand in hand. They are not the same thing. But they are necessarily linked, and complementary. Any effort to separate the two is likely to cause more problems than it solves.